Analysis of the Rayleigh number in the area of steel rectangular sections in the conditions of stedy and unstedy heat flow = Analiza liczby Rayleigha w obszarze stalowych profili prostokątnych w warunkach ustalonego i nieustalonego przepływu ciepła - Wyczółkowski, Rafał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the experimental measurements dedicated to the research for the Rayleigh number (Ra) in the area of rectangular steel sections. This problem is associated with the analysis of the free convection which takes place in the heating of sections bundles during the heat treatment.
Keywords: liczba Rayleigha; konwekcja swobodna; profile stalowe; obróbka cieplna; Rayleigh number; free convection; steel section; heat treatment